Buckling of elastic columns with initial imperfections and load eccentricity. (February 2020) - Harvey, P.S.; Cain, T.M.N.
Abstract: Imperfections in buckling analyses are often assumed to take the form of either initial member imperfections or load eccentricity, but these effects are typically treated separately. In this paper, these two imperfections are treated simultaneously, focusing on the case in which the two effects neutralize each other. A linear analysis is performed to determine the critical ratio of load eccentricity to member imperfection amplitude at which the column switches its direction of buckling. The results are validated through a series of experimental tests leveraging the capability of 3D-printing to incorporate prescribed geometric imperfections.